RUMINAL FERMENTATION KINETICS OF MORINGA AND PELTIPHYLLUM SUPPLEMENTS DURING EARLY INCUBATION PERIOD IN THE IN VITRO READING PRESSURE TECHNIQUE - Jayanegara, A.; Sabhan, T.; Takyi, A.K.; Salih, A.O.; Hoffmann, E.M. (Journal of the Indonesian Tropical Animal Agriculture, 2010)
This experiment was aimed to observe rumen fermentation kinetics of alternative supplements, i.e.Moringa oleifera and Peltiphyllum peltatum leaves added to maize silage diet as compared to aconventional supplement (barley-soya). A total of six treatments were investigated in the present study,which consisted of: maize silage (A), M. oleifera (B), P. peltatum (C), maize silage + concentrate (56:44,w/w; D), maize silage + M. oleifera (56:44, w/w; E), and maize silage + concentrate + P. peltatum(47:37:16, w/w/w; F). The feeds were incubated in vitro in three replicates (completely randomized)using the Reading Pressure Technique system. Approximately 800 mg of the feeds were mixed by 75 mlof buffered rumen liquor. The incubation was carried out up to 12 h in bottles and gas pressure wasrecorded and released in regular intervals. Repeated sampling was conducted for analysis offermentation products at 1, 6 and 12 h of incubation period. The results showed that the nutritionalquality of Moringa and its fermentation pattern was comparable to that of barley-soya concentrate. PlainMoringa incubation resulted the highest production of iso-SCFA and soluble protein concentrationamong all treatments after 12 h incubation (P<0.05). Incubation of sole Peltiphyllum peltatum highlyhampered the fermentation rate. Production of iso-SCFA both for plain Peltiphyllum and its mixturewere comparatively low. Supplementation of Peltiphyllum increased significantly soluble proteinconcentration during 12 h incubation (P<0.05). Peltiphyllum also had a very low C2+C4/C3 ratiocompared to other treatments. It could be concluded that Moringa oleifera is a potential alternativesupplement to replace either partially or completely concentrate as a conventional supplement, andPeltiphyllum peltatum supplementation could reduce excessive protein degradation and fermentation ofthe concentrate in the rumen.